Diagnóstico da gestão de resíduos sólidos urbanos de sete municípios da região metropolitana de Maringá - Paraná - Moraes, Eliene (2011)
This paper presents the diagnosis of municipal solid waste management (MSWM) developed in seven municipalities in the Maringa's Metropolitan Region - Angle, Astorga, Mandaguaçu, Marialva Paiçandu, Sarandi - and Maringa City polo, Paraná State. For the diagnosis applies a questionnaire, supplemented by interviews with staff responsible for visits in site and with photographic records. Quantitative data was collected of waste generated and system of MSWM, addressing household waste, commercial and health services, construction, urban sanitation and disposal, among others. This diagnosis was established that the seven counties showed have deficiencies throughout the system occasioned by lack of organization, control, planning and operational services appropriate result of lack of investment, technical personnel trained, infrastructure and equipment. Among these deficiencies, there is final disposal that even the four cities that have landfills, because of these deficiencies are turning dumps. However, we highlight the experience of the city of Sarandi is providing his MSW in a landfill and is recovering the area of old dump, and the experience Astorga City, with its selective collection program.